Pengaruh Pendidikan Kewirausahaan Terhadap Intensi Berwirausaha Dengan Self-Efficacy Sebagai Variabel Intervening - Fadhila Alfaini; Arwin Sanjaya (LPPM Universitas Multi Data Palembang, 2023)
This study aims to determine the effect of Entrepreneurship Education on Entrepreneurial Intentions withSelf-Efficacy as a mediator. Data were analyzed by path analysis. The number of samples was 85 student respondentsfrom the Faculty of Economics & Business, Mulawarman University class of 2018 who had taken entrepreneurshipcourses. This study found that entrepreneurship education has a significant effect on entrepreneurial intentions,entrepreneurship education has a significant effect on self-efficacy, self-efficacy has a significant effect on entrepreneurial intentions, entrepreneurship education has a significant effect on entrepreneurial intentions through selfefficacy.